2019
DOI: 10.4314/tjpr.v18i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge and attitude of patients on herbal medicine use in Udupi region, Karnataka, India

Abstract: Purpose: To determine the knowledge and attitude of patients on the usage of herbal medicines in Udupi Region of Karnataka State, India. Methods: This was a descriptive, cross-sectional study, carried out over a period of six months, and involving a structured and validated questionnaire. It was conducted among patients who visited hospitals in and around the Udupi region of Karnataka, India. Results: About 37 % of the respondents of the study used a combination of allopathy and herbal medicines. The results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“… Inadequacy in the knowledge of the common public to accept risks from wrong practices and misconceptions of use of homoeopathic medicines. 41…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Inadequacy in the knowledge of the common public to accept risks from wrong practices and misconceptions of use of homoeopathic medicines. 41…”
Section: Discussionmentioning
confidence: 99%
“…Inadequacy in the knowledge of the common public to accept risks from wrong practices and misconceptions of use of homoeopathic medicines. 41 Lack of knowledge, attitude and practices of PV among homoeopathic professionals. [42][43][44] Misleading and Objectionable advertisement: Publicising improper drug information in the form of advertisements is another matter of concern that needs to be addressed to safeguard the interest of homoeopathic drug consumers.…”
Section: Pharmacovigilance In Homoeopathy Singh 33mentioning
confidence: 99%
“…Herbal products are intended to be used for medicinal and therapeutic purposes through patients. In various studies, it is stated that about half of the participants use at least one herbal product (Mosihuzzaman, 2012;Kıssal et al, 2017;Bhat et al, 2019;Chopra and Dhingra, 2021). It has been well observed that patients have had a strong belief in the healing power of natural herbs since ancient times (WHO, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…[11]. Bhat et al (2019) reported that patients mostly prefer herbal products over conventional medicines since they think that these products are more efficacious and have minimal side effects. In the same study, patients' major sources of information regarding herbal medicines were friends and advertisements [12].…”
Section: Introductionmentioning
confidence: 99%
“…Bhat et al (2019) reported that patients mostly prefer herbal products over conventional medicines since they think that these products are more efficacious and have minimal side effects. In the same study, patients' major sources of information regarding herbal medicines were friends and advertisements [12]. A study from Turkey showed that participant's knowledge on herbal products depends on advertisements through media and herbal products are usually purchased from herb sellers [13].…”
Section: Introductionmentioning
confidence: 99%